Developing Problem-Based Learning Module For Biotechnology Concepts - Ahmad Yani; Sahriah Sahriah; Romi Adiansyah (Pascasarjana Universitas Negeri Malang (UM), 2017)
Abstract: This study attempted to develop and know the effectiveness of PBL module for biotechnology concepts intended for high school students. Brog and Gall model was referred as the framework to develop the product. It comprises some stages, namely, analyzing potential and problems, collecting information, developing the module’s initial design, validating the design, revising the design, and trying out the product. The appointed experts in product development and learning as well as high school biology teachers in Biology Teachers’ Association (MGMP) validated the product. The validation showed that the product is practical and valid to be used. The module is also effective for learning, as evidenced by the PBL activities reaching “high” category and by the improvement of the students’ cognitive domain represented in the improvement of the initial average score.Key Words: problem-based learning module, cognitive learning outcomes, biotechnology conceptsAbstrak: Penelitian ini bertujuan untuk mengembangkan dan mengetahui efektivitas modul pembelajaran berbasis masalah untuk SMA pada konsep Bioteknologi. Model pengembangan merujuk dari Brog dan Gall. Tahapan pengembangan terdiri atas analisis potensi dan masalah, pengumpulan informasi, penyusunan desain awal modul, validasi desain, revisi desain, dan ujicoba produk. Validasi produk dilakukan oleh Pakar Pengembangan, Pembelajaran dan guru Biologi SMA melalui kegiatan Musyarawah Guru Mata Pelajaran (MGMP) Biologi. Hasil penilaian pakar menunjukkan bahwa modul yang dikembangkan valid dan praktis untuk digunakan. Modul ini juga efektif digunakan dalam pembelajaran, aktivitas PBL mencapai kategori “tinggi”, serta meningkatkan hasil belajar kognitif peserta didik.Kata kunci: modul pembelajaran berbasis masalah, hasil belajar kognitif, konsep bioteknologi